Penatausahaan Barang Milik Daerah (BMD): Kajian pada Badan Pendapatan Daerah, Kantor Dinas Olahraga Dan Pemuda - Azzahra, Fatimah; Daulay, Nur Asri Elita; Putranta, Jeremi; Allim, Syamsul (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
Among the case studies of the main issues of collective property management are the misappropriation of property by others according to established procedures, irregular record-keeping, inadequate resources, and the inclusion of unclear ownership. The study identified factors that hamper asset management remained the solution. The study USES qualitative methods with a case-study approach. The type of data used by the authors in this study is the data of literature studies. The data for writing this library review is obtained by locating a paper collected using the Google school database and the journal website and available paper that can be given on the problem: 1. Increasing surveillance 2. Increase human resources 3. Increasing community participation 4. Improving inter-office cooperation from case studies presented in the study, it seems that regional real estate management in the areas is still less than optimal. The main causes of problems for management of local assets are the lack of the capacity and integrity of human resources and the capacity of the management staff of a number of local assets, thus not well processed reporting and inventory of local assets. .